A Chinese Family With Adult-Onset Leigh-Like Syndrome Caused by the Heteroplasmic m.10191T>C Mutation in the Mitochondrial MTND3 Gene - Li, Tao-Ran; Wang, Qun; Liu, Mao-Mao; Lv, Rui-Juan (Frontiers in Neurology, 2019)
Leigh syndrome (LS) is a mitochondrial disease of infancy and early childhood, that is rarely seen in adults. The high degree of genetic and clinical heterogeneity makes LS a very complex syndrome. The clinical manifestations include neurological symptoms and various non-neurological symptoms, with different mutations differing in presentations and therapies. The m.10191T>C mutation in the mitochondrial DNA gene encoding in the respiratory chain complex I (CI) subunit of MTND3 results in the substitution of a highly conserved amino acid (p.Ser45Pro) within the ND3 protein, leading to CI dysfunction and causing a broad clinical spectrum of disorders that includes LS. Patients with the m.10191T>C mutation are rare in general, even more so in adults. In the present study, we report a family of patients with very rare adult-onset Leigh-like syndrome with the m.10191T>C mutation. The 24-year-old proband presented with seizures 6 years ago and developed refractory status epilepticus on admission. She had acute encephalopathy accompanied by lactic acidosis, symmetrical putamen and scattered cortical lesions. The video electroencephalogram suggested focal-onset seizures. She harbored the heteroplasmic m.10191T>C mutation in her blood and fibroblasts. Her aunt was diagnosed with mitochondrial disease at the age of 42, and had the heteroplasmic m.10191T>C mutation in her fibroblasts. Her aunt's son (cousin) died of respiratory failure at the age of 8, and we suspected he was also a case of LS. Furthermore, we reviewed the previously reported patients with the m.10191T>C mutation and summarized their characteristics. Recognizing the characteristics of these patients will help us improve the clinical understanding of LS or Leigh-like syndrome.